Survival benefit of gastrectomy for gastric cancer with peritoneal carcinomatosis: a propensity score‐matched analysis. (20th September 2016) - Geng, Xiuwen; Liu, Hao; Lin, Tian; Hu, Yanfeng; Chen, Hao; Zhao, Liying; Mou, Tingyu; Qi, Xiaolong; Yu, Jiang; Li, Guoxin
Abstract: Peritoneal carcinomatosis (PC) is the most frequent pattern of metastasis in stage IV gastric cancer (GC). The study aims to investigate the efficacy of gastrectomy in GC with PC. Clinicopathological data of 518 stage IV GC patients were retrospectively collected in Nanfang Hospital. Among all cases, 312 GC patients with PC (without other site of metastasis) were eligible. Univariate and multivariate analyses were performed to identify the independent prognostic factors. Propensity score matching analysis was performed to balance the characteristics and treatment‐related factors. There was a significantly improved overall survival in gastrectomy group (148 patients) compared with nonresection group (164 patients) ( P  <   0.001). The 1‐year and 2‐year survival rates were 49.8% and 21.5% in gastrectomy group, whereas 28.8% and 9.7% in nonresection group, respectively. Further analysis showed that gastrectomy had also improved survival in P1 ( P  =   0.017) and P2 stage patients ( P  <   0.001), but not P3 stage ( P  =   0.495). The modality of gastrectomy plus chemotherapy plus hyperthermic intraperitoneal chemotherapy (HIPEC) showed an optimum survival. In addition, P3 disease, nongastrectomy, nonchemotherapy, non‐HIPEC, and age ≥ 60 years were independently associated with poor survival. The gastrectomy plus chemotherapy plus HIPEC modality showed a significant survival benefit for gastric adenocarcinoma patients, particularly in those with P1 and P2 diseases. Abstract : The gastrectomy plus chemotherapy plus hyperthermic intraperitoneal chemotherapy (HIPEC) modality showed a significant survival benefit for gastric adenocarcinoma, particularly in those with P1 and P2 diseases. These results may shed light on the role of adjuvant surgery on the treatment of stage IV gastric cancer with peritoneal carcinomatosis.